Hyperpolarized 129Xe imaging of embryonic stem cell‐derived alveolar‐like macrophages in rat lungs: proof‐of‐concept study using superparamagnetic iron oxide nanoparticles. Issue 4 (25th September 2019) - Riberdy, Vlora; Litvack, Michael; Stirrat, Elaine; Couch, Marcus; Post, Martin; Santyr, Giles E.
Abstract : Purpose: To measure regional changes in hyperpolarized 129 Xe MRI signal and apparent transverse relaxation ( T 2 ∗ ) because of instillation of SPION‐labeled alveolar‐like macrophages (ALMs) in the lungs of rats and compare to histology. Methods: MRI was performed in 6 healthy mechanically ventilated rats before instillation, as well as 5 min and 1 h after instillation of 4 million SPION‐labeled ALMs into either the left or right lung. T 2 ∗ maps were calculated from 2D multi‐echo data at each time point and changes in T 2 ∗ were measured and compared to control rats receiving 4 million unlabeled ALMs. Histology of the ex vivo lungs was used to compare the regional MRI findings with the locations of the SPION‐labeled ALMs. Results: Regions of signal loss were observed immediately after instillation of unlabeled and SPION‐labeled ALMs and persisted at least 1 h in the case of the SPION‐labeled ALMs. This was reflected in the measurements of T 2 ∗ . One hour after the instillation of SPION‐labeled ALMs, the T 2 ∗ decreased to 54.0 ± 7.0% of the baseline, compared to a full recovery to baseline after the instillation of unlabeled ALMs. Histology confirmed the co‐localization of SPION‐labeled ALMs with regions of signal loss and T 2 ∗ decreases for each rat. Conclusion: Hyperpolarized 129 Xe MRI can detect the presence of SPION‐labeled ALMs in the airways 1 h after instillation. This approach is promising for targeting and tracking of stem cells for the treatment of lung disease.